Reliability of 4D Flow MRI for Investigation of Fetal Cardiovascular Hemodynamics in the Third Trimester - Englund, Erin K.; Fujiwara, Takashi; Smith, Sarah A.; Meyers, Mariana L.; Friesen, Richard M.; Browne, Lorna P.; Barker, Alex J. (Radiology. Cardiothoracic imaging, 2024)
Four-dimensional flow MRI was feasible in third-trimester fetuses, and hemodynamic measurements were precise across measurement locations, internally consistent based on conservation of mass, repeatable from test-retest data, and correlated to two-dimensional phase contrast MRI measurements.